Shakespeare & Hathaway : private investigators. Season two [videorecording (DVD)] - Joyner, Jo, 1977-; Benton, Mark, 1965-; McBride, Patrick Walshe; Aga, Amber (BBC, 2019)
The hilariously mismatched detective duo of Luella Shakespeare and grumpy Frank Hathaway return for ten more episodes of the hit mystery/comedy- drama set in beautiful Stratford-upon-Avon. One might think the birthplace of William Shakespeare would be safe from fraud, extortion, vice, identity theft, and ransom, but they would be wrong.